Labor and American Politics - Boivin, Jean (Relations Industrielles / Industrial Relations, 1979)
This article reviews the book, "Labor and American Politics," by Charles M. Rehmus, Doris B. McLaughlin & Frederic H. Nesbitt, Revised.